English as a Medium of Instruction on the Arabian Peninsula - Wyatt, Mark; El Gamal, Glenda (Taylor & Francis, 2023)
Focusing on English as a Medium of Instruction (EMI) in the Arab Gulf states, the authors consider both sociolinguistic and pedagogical perspectives, and explore practical implications. // This edited volume features chapters covering how teachers are negotiating the linguistic challenges posed by EMI; issues of ownership, choice and agency; the scaffolding of academic literacies; how to support the development of content teachers' pedagogical content knowledge in EMI settings as well as the benefits of a bilingual education. Chapter authors all have extensive local experience that they draw upon reflectively in their writing. Policy-makers, teachers and teacher educators wondering how they can best balance the need to develop competence in English in students of all ages on the Arabian Peninsula in a globalizing world, together with the concern to nurture Arabic language, culture and identity, will gain rich insights from this book. // Postgraduates and researchers exploring issues surrounding EMI, both locally and internationally, will benefit from the arguments presented in this volume.